Sheng-Mai San extracts attenuate heart injury in chronic intermittent hypoxia via suppressing oxidative damage and regulating glucose metabolism - Chunhua Liu; Yaqian Feng; Dazheng Zhou; Aichun Ju; Junping Kou; Boyang Yu; Jin Qi (Pharmacological Research - Modern Chinese Medicine, 2022)
Background: Sheng-Mai San extracts (SMSE), derived from a Chinese medicine formula Sheng-Mai San, benefits prevention and treatment of cardiovascular disease. However, it remains unknown how SMSE exerts its effects on chronic intermittent hypoxia (CIH)-induced heart injury. Objective: This study aims to evaluate the efficacy of SMSE on CIH-induced heart injury by suppressing oxidative damage and promoting glucose energy metabolism. Methods: The CIH-induced model was established through the mice being placed in a hypoxic chamber with 7 to 8% O2. Then, such indexes as cardiac function, histopathological changes, creatine kinase (CK), superoxide dismutase (SOD) and myeloperoxidase (MPO) and malondialdehyde (MDA) were measured. Lastly, the influence on energy metabolism was explored through determining the ratio of ATP/ADP, concentrations of pyruvate and lactic acid, ATPase activities and levels of proteins including pyruvate kinase M2 (PKM2), fructose 6-phosphate kinase (6-FPK) and pyruvate dehydrogenase kinase 4 (PDK4). Results: SMSE could obviously improve cardiac function and histopathological changes of heart tissue; reduce CK and MPO activities as well as MDA and lactic acid contents; increase SOD and ATPase activities, the ratio of ATP/ADP and pyruvate concentration; and regulate the protein expression of PKM2, 6-FPK and PDK4. Conclusion: SMSE could attenuate CIH-induced heart injury via suppressing oxidative damage and regulating glucose metabolism.